MiR-374b increases the CIK expression and mediates biological function changes in cervical cancer cells by targeting the PD-1/PD-L1 signaling pathway. (February 2021) - Wang, Chunyan; Kuang, Lei; Han, Liwei
Highlights: miR-374b was highly expressed in cervical cancer. miR-374b can increase the expression of CIK cells by targeting PD-1 to affect the PD-1/PD-L1 signaling pathway.t miR-374b can target PD-1 to mediate the PD-1/PD-L1 signaling pathway and enhance the function of CIK cells. Abstract: Objective: To investigate the role of miR-374b in medicating biological function changes in cervical cancer cells by increasing the cytokine-induced killer (CIK) expression. Methods: Venous blood of 62 cervical cancer patients and 58 healthy individuals including Human cervical cancer cell line (HeLa) and normal human uterine smooth muscle cells (HUSMC) were tested for expression of miR-374b, PD-1, and PD-L1. sh-PD-1, si-PD-1, NC, miR-374b-inhibitor, and miR-374b-mimics were transfected into HeLa cells, and expression of miR-374b, PD-1, and PD-L1 was determined by a qRT-PCR assay, and the proliferation and apoptosis of the cells were detected using a MTT assay and flow cytometry, respectively. Results: PD-1 was highly expressed in cervical cancer, while miR-374b is lowly expressed in it, and the area-under-the-curve (AUC) of both PD-1 and miR-374b was larger than 0.8. The dual luciferase reporter assay confirmed relationship between PD-1 and miR-374b. Expression of PD-1 in HeLa cells was significantly down-regulated after transfection of miR-374b-mimics. Compared with the CIK + NC group, the CIK + miR-374b-mimics group and the CIK + siRNA-PD-1 group showed a significant decrease in the relative mRNA expression of PD-1, compared with other group showed significantly lowered activity of HeLa cells, and the two groups showed significantly reduced tumor volume. Conclusion: MiR-374b increases the CIK expression and mediates biological function changes in cervical cancer cells by targeting the PD-1/PD-L1 signaling pathway, so it is expected to be a potential therapeutic target for cervical cancer.